2016
DOI: 10.1111/iej.12727
|View full text |Cite
|
Sign up to set email alerts
|

A re‐audit of the technical quality of undergraduate root canal treatment after the introduction of new technology and teaching practices

Abstract: Changes to endodontic teaching practices significantly improved the technical standards of undergraduate root filling in multirooted teeth. The regular auditing of undergraduate teaching practice is necessary to inform current teaching, instigate change and improve standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 29 publications
5
37
0
4
Order By: Relevance
“…Furthermore, the results also showed that the students performed root canal treatments in both single and multirooted teeth. The findings are similar to those reported by Lynch & Burke (2006) who assessed the technical quality of root canal treatment in single-rooted teeth in Ireland and to those of Donnelly et al (2016) who used similar canal preparation technology for root canal treatment to the ones used in the current audit. Results of similar clinical audits, however, from other UK dental schools have found acceptable root filling rates as high as 80% and as low as 13%, respectively (Hayes et al 2001, Pettigrew et al 2007.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the results also showed that the students performed root canal treatments in both single and multirooted teeth. The findings are similar to those reported by Lynch & Burke (2006) who assessed the technical quality of root canal treatment in single-rooted teeth in Ireland and to those of Donnelly et al (2016) who used similar canal preparation technology for root canal treatment to the ones used in the current audit. Results of similar clinical audits, however, from other UK dental schools have found acceptable root filling rates as high as 80% and as low as 13%, respectively (Hayes et al 2001, Pettigrew et al 2007.…”
Section: Discussionsupporting
confidence: 89%
“…different whether performed on anterior or posterior tooth and this may be related to the use of rotary NiTi instrumentation as shown by Donnelly et al (2016) where the treatment outcome for posterior teeth has improved with the introduction of such technology. However, it is also likely that the limitation of periapical radiographs in assessing the quality of root fillings in posterior teeth may have overestimated the outcome compared to anterior teeth.…”
Section: Accepted Articlementioning
confidence: 99%
“…From the updated search, one study was included for full‐text reading, although the RCT was performed by mechanized instrumentation (Donnelly et al . ), making it not eligible for inclusion. From these remaining studies, 28 were subsequently excluded (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used radiographic assessment of the technical quality of root fillings as criteria to audit the overall quality of treatment conducted by undergraduate students in various populations (Eleftheriadis & Lambrianidis , Donnelly et al . ). The technical quality parameters mainly assessed were the length of the root filling material in relation to the radiographic apex, the density of the filling material (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation